PENGARUH KEMAMPUAN MENGHAFAL AL-QUR'AN TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM KELAS IX: SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL FALAAH SIMO BOYOLALI TAHUN PELAJARAN 2023/2024 - Aisyatun Nisa, Asma; Hidayah, Nur; Eko Rochmawan, Alfian (QATHRUNÂ, 2023)
Memorizing Al-Qur'an Memorizing Al-Qur'an is a process of reading Al-Qur'an then instilling each reading into brain memory. the researcher wants to test whether memorizing the Qur'an is a good factor for learning achievement in Class IX Islamic Religious Education at SMP IT Falah Boyolali. This study used a quantitative research type with a sample of 61 Class IX students at SMP IT Al Falah Boyolali. In collecting research data using questionnaires to students and documentation. The analysis technique for testing the validity of the reliability test, the classical assumption test, and the simple regression test uses the SPSS application. The results showed that based on the results of the tests conducted, it can be concluded that the effect of memorizing the Qur'an on student achievement at SMP IT Al Fallah Boyolali with the results of the hypothesis test using the IBM SPSS Version 25 program in the ANOVA table obtained a significance value of 0.002 <0.05, so hypothesis testing explained that H1 is accepted and H0 is rejected in other words that there is a significant effect of memorizing the Qur'an on PAI Learning Achievement of class IX SMP IT Al Falah Boyolai. With a coefficient of determination of 14.9%, it has a positive effect, meaning that the higher the students memorize the Al-Qur'an, the higher the learning outcomes obtained by students. While the rest are factors that influence the variable (Y) learning outcomes from other factors not examined in this study.